2008
DOI: 10.1111/j.1365-2222.2008.03061.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Lactobacillus rhamnosus or Bifidobacterium lactis probiotics in pregnancy increases cord blood interferon‐γ and breast milk transforming growth factor‐β and immunoglobin A detection

Abstract: The findings suggest that supplementation with probiotics in pregnancy has the potential to influence fetal immune parameters as well as immunomodulatory factors in breast milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 38 publications
9
157
2
2
Order By: Relevance
“…Previous studies have shown that probiotic supplementation during lactation increases the IgA levels in human milk and mouse milk. 21,22) However, there is a concern that probiotic consumption has the potential to cause systemic infections, which has been supported by several reports of safety concerns relating to probiotic use in immunocompromised hosts such as infants and pregnant women. Another concern is that probiotic bacteria cannot function as efficiently as desired in the absence of prebiotics, which are nondigestible dietary components that beneficially affect the host by selectively stimulating the growth and/or activity of one type or a limited number of types of bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that probiotic supplementation during lactation increases the IgA levels in human milk and mouse milk. 21,22) However, there is a concern that probiotic consumption has the potential to cause systemic infections, which has been supported by several reports of safety concerns relating to probiotic use in immunocompromised hosts such as infants and pregnant women. Another concern is that probiotic bacteria cannot function as efficiently as desired in the absence of prebiotics, which are nondigestible dietary components that beneficially affect the host by selectively stimulating the growth and/or activity of one type or a limited number of types of bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence of increased CRP, total IgE, and IL-10 levels, which are characteristic of a low-grade inflammation has been presented [66]. Another study decreased that after supplementation during pregnancy with L. rhamnosus and B. lactis, IFN-γ in cord blood increased [67]. Anti-CD3/CD28-induced IL-2 mRNA expression at 13 months of age was showed after probiotic supplementation at weaning [68].…”
Section: What Are the Mechanisms Behind Probiotics In Allergy Preventmentioning
confidence: 90%
“…Было показано, что прием некоторых пробиоти-ческих штаммов, принадлежащих к разным видам, таких как Lactobacillus rhamnosusor Bifidobacterium animalis subsp. lactis, на поздних сроках беременности и/или грудное вскармливание увеличивает IgA и уровни TGF-β2 в моло-ке [28,29]. Увеличение уровней IgA может помочь ограни-чить доступ бактерий, вызывающих мастит, в эпителий молочной железы, а TGF-β2 является ключевым иммуно-регуляторным фактором молочной железы, способствую-щим локальной выработке IgA и стимулирующим меха-низмы пероральной толерантности у младенцев.…”
Section: мастит: мишень для пробиотиков?unclassified